Cell-free HPV-DNA as a high-accuracy biomarker for treatment de-escalation in HPV-positive head and neck squamous cell carcinoma - Hollander, Alex; Nonaka, Taichiro (Frontiers in Oncology, 2025)
ObjectiveHead and neck squamous cell carcinoma (HNSCC) remains a devastating disease with significant morbidity and mortality, despite advances in treatment. HPV-positive HNSCC, in particular, has been increasing in incidence worldwide, yet optimal management strategies remain an unmet need. While patients with HPV-positive tumors have a better prognosis and improved response to therapy compared to HPV-negative cases, the long-term toxicities associated with standard treatments necessitate a shift toward treatment de-escalation strategies. However, the lack of biomarkers to guide patient selection for de-intensified therapy remains a critical challenge. We hypothesize that cell-free HPV-DNA (cfHPV-DNA) demonstrates high diagnostic accuracy and can serve as an effective non-invasive biomarker for early detection, disease monitoring, and treatment de-escalation in HPV-positive HNSCC. This meta-analysis aims to establish the clinical utility of cfHPV-DNA in diagnosing HNSCC and its potential role in guiding de-escalation strategies.MethodsA comprehensive literature search was conducted using PubMed, Web of Science, and Wiley to identify studies evaluating the diagnostic value of cfHPV-DNA in HNSCC. The population included HPV-positive HNSCC patients, the intervention was cfHPV-DNA detection via liquid biopsy, and the outcome was to assess the diagnostic performance of cfHPV-DNA. The pooled diagnostic parameters were analyzed using STATA and Revman.ResultsTwelve studies involving 626 patients were included. The pooled sensitivity and specificity of cfHPV-DNA were 0.89 (95% CI: 0.71 – 0.96) and 0.99 (95% CI: 0.91 – 1.00), respectively. The positive and negative likelihood ratios were 66.55 (95% CI: 8.9 – 497.6) and 0.12 (95% CI: 0.04 – 0.33), with a pooled diagnostic odds ratio of 574.73 (95% CI: 55 – 6019). The area under the curve (AUC) was 0.98 (95% CI: 0.96 – 0.99), indicating exceptional diagnostic performance.ConclusionThe high diagnostic accuracy of cfHPV-DNA supports its potential as a valuable biomarker for early detection and risk stratification in HPV-positive HNSCC. Our findings suggest that cfHPV-DNA could provide a real-time, non-invasive tool to monitor treatment response and disease progression, allowing for personalized de-escalation approaches. Furthermore, we discuss the necessary steps toward FDA approval, emphasizing the need for standardized detection methods and large-scale validation studies to facilitate its integration into clinical practice.